Computational analysis and design of an aerofoil with morphing tail for improved aerodynamic performance in transonic regime - Rana, Zeeshan; Mauret, F.; Sánchez Gil, Jesús Miguel; Zeng, Kai; Hou, Z.; Dayyani, Iman; Könözsy, László Z. (Cambridge University Press, 2022)
This article focuses on the aerodynamic design of a morphing aerofoil at cruise conditions using computational fluid dynamics (CFD). The morphing aerofoil has been analysed at a Mach number of 0.8 and Reynolds number of 3×106 , which represents the transonic cruise speed of a commercial aircraft. In this research, the NACA0012 aerofoil has been identified as the baseline aerofoil where the analysis has been performed under steady conditions at a range of angles of attack between 0∘ and 3.86∘ . The performance of the baseline case has been compared to the morphing aerofoil for different morphing deflections ( wte/c=[0.005−0.1] ) and start of the morphing locations ( xs/c=[0.65−0.80] ). Further, the location of the shock wave on the upper surface has also been investigated due to concerns about the structural integrity of the morphing part of the aerofoil. Based upon this investigation, a most favourable morphed geometry has been presented that offers both, a significant increase in the lift-to-drag ratio against its un-morphed counterpart and has a shock location upstream of the start of the morphing part.
Keywords: Morphing aerofoil; CFD; aerodynamics; transonic flow; shock waves